Biophysical Characterization of the Oligomeric States of Recombinant Immunoglobulins Type-M and Their C1q-Binding Kinetics by Biolayer Interferometry - Chouquet, Anne; Pinto, Andrea J.; Hennicke, Julia; Ling, Wai Li; Bally, Isabelle; Schwaigerlehner, Linda; Thielens, Nicole M.; Kunert, Renate; Reiser, Jean-Baptiste (Frontiers in Bioengineering and Biotechnology, 2022)
Immunoglobulins type-M (IgMs) are one of the first antibody classes mobilized during immune responses against pathogens and tumor cells. Binding to specific target antigens enables the interaction with the C1 complex which strongly activates the classical complement pathway. This biological function is the basis for the huge therapeutic potential of IgMs. But, due to their high oligomeric complexity, in vitro production, biochemical characterization, and biophysical characterization are challenging. In this study, we present recombinant production of two IgM models (IgM617 and IgM012) in pentameric and hexameric states and the evaluation of their polymer distribution using different biophysical methods (analytical ultracentrifugation, size exclusion chromatography coupled to multi-angle laser light scattering, mass photometry, and transmission electron microscopy). Each IgM construct is defined by a specific expression and purification pattern with different sample quality. Nevertheless, both purified IgMs were able to activate complement in a C1q-dependent manner. More importantly, BioLayer Interferometry (BLI) was used for characterizing the kinetics of C1q binding to recombinant IgMs. We show that recombinant IgMs possess similar C1q-binding properties as IgMs purified from human plasma.